Portable electronic assistive technology to improve vocational task completion in young adults with an intellectual disability: A review of the literature. (September 2018) - Collins, James C; Collet-Klingenberg, Lana
This article summarizes a review of empirical literature from 2000 to 2015 that involved the use of specific portable technology to support persons with an intellectual disability in completing work-related tasks. Nineteen studies were identified for review, with an emphasis on the identification of (a) the characteristics of participants and settings, (b) the types of portable technology and prompting formats used, (c) the research designs utilized, (d) the independent and dependent variables, (e) the measures of reliability and validity, and (f) the overall effectiveness of the interventions. The authors provide an interpretation of the findings as well as the implications of the results and recommended areas for future research.